Analisis Kesiapan Petani terhadap Pemanfaatan Marketplace untuk Penjualan Hasil Tani di Desa Parakan - Salma Rizqiany Lubis; Intan Latifah; Eidelweis Restu; Muhammad Adlan; Lutfi Shihab; Rizha Nur Irawan; Agief Julio Pratama; M. Iqbal Nurulhaq; Tri Budiarto; Widya Hasian Situmeang; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
This study aims to analyze the readiness of farmers in Parakan Village to utilize digital platforms for marketing agricultural products. The methods used include interviews, focus group discussions (FGDs), mentoring, and the distribution of questionnaires to 30 members of the Mawar Farmer Group. Findings indicate a shift in farmers' behavior from relying on middlemen to independently marketing their products through social media. However, survey results show low levels of information access, active participation, and understanding of digital innovation. Innovation and digital literacy are key challenges, although some farmers expressed a willingness to learn. Continuous mentoring and collaboration between farmers, academics, and the government are essential to support an inclusive and sustainable digital transformation in the agricultural sector.